Perception of young people aged 20 to 30 of labor inclusion in a city (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2023)
This is a quantitative descriptive study referring to labor inclusion and perception of situations of inclusion or discrimination at work. Carried out with people between the ages of 20 and 30, where it is reflected that the perception of non-inclusion is detected more towards others than towards the respondents. More than half declare inclusion as employment integration, rights, equality and acceptance without including any concept of gender in the declaration. More than 60% of respondents have witnessed non-inclusion in others because of image or appearance, 59% because of the person's physique, and 55.5% because of gender or gender orientation. Almost a quarter of the respondents have suffered from being discriminated against because of their appearance or image, because of their physique or because they are a woman. There is a statistically significant difference between the perceptions of another and the experience of non-inclusion events, highlighting the first (the perception of the other) and therefore an implicit and non-explicit statement of the existence of non-inclusion in the research environment.
Keywords: Inclusion; Perception; Rights